Implementation of Al-'Aṣā An-Nāṭiqah Media in Arabic Speaking Skills - Ridwan, Mohammad Ridwan Syafi'i; Nurrokhmatulloh, Nurrokhmatulloh; Syarifuddin , Syarifuddin (Study Program of Arabic Language Teaching, 2025)
This study aims to explore how the use of al-‘aṣā an-nāṭiqah contributes to improving students’ Arabic speaking skills by examining their responses during the learning process. This study used a descriptive qualitative method to focus on students of class XA MA Darut. Data were collected through classroom observation, structured interviews, and relevant documentation. The data analysis focused primarily on teacher interviews to evaluate the application and impact of this media. The collected data were analyzed using an interactive model consisting of data reduction, data display, and conclusion verification. Through this process, the researcher identified key themes, patterns, and insights related to implementing al-‘aṣā an-nāṭiqah in enhancing students’ speaking skills. The findings reveal that integrating al-‘aṣā an-nāṭiqah positively influences students’ interest and participation in speaking activities, thereby significantly improving their maharah kalam. This study highlights the value of using interactive and student-centered teaching tools to enhance Arabic speaking skills. Such approaches promote greater student engagement, motivation, and participation, essential in fostering communicative competence. The findings provide useful insights for educators aiming to improve speaking instruction through innovative media.